2001
DOI: 10.1007/s007020170102
|View full text |Cite
|
Sign up to set email alerts
|

No association between dopamine D2 receptor gene (DRD2) and human intelligence

Abstract: Significantly diminished intellectual functioning, as indicated by appropriately administered IQ tests with scores below 70, is a frequent mental handicap leading to severe social disadvantages and serves as a paradigm for molecular genetic research of complex disorders and traits due to its multitude of known and unknown, genetic as well as environmental causes. Since the number of confounding variables is expected to be considerably reduced in the normal population at the opposite ends of the IQ distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…In previous studies, DRD2 rs1800497 was found to not be associated with intelligence in middle-aged adults (Moises et al 2001), whereas it was associated with increased IQ in a study of young women (Tsai et al 2002). The A1(T) (Welton et al 2008) allele was associated with better performance in immediate and delayed memory and MMSE in a population with age-related cognitive impairment (Bartres-Faz et al 2002).…”
Section: Drd2mentioning
confidence: 92%
“…In previous studies, DRD2 rs1800497 was found to not be associated with intelligence in middle-aged adults (Moises et al 2001), whereas it was associated with increased IQ in a study of young women (Tsai et al 2002). The A1(T) (Welton et al 2008) allele was associated with better performance in immediate and delayed memory and MMSE in a population with age-related cognitive impairment (Bartres-Faz et al 2002).…”
Section: Drd2mentioning
confidence: 92%
“…However, results based on the DRD2 gene are mixed. An early study linked the A1 allele to reduced cognitive ability (Berman and Noble 1995) but subsequent work has failed to corroborate these findings (Moises 2001, Petrill 1997. Studies of nonhuman subjects have shown activation of D2 receptors improves acquisition and retention of working memory tasks (Missale et al 1998).…”
Section: Dopamine and The D2mentioning
confidence: 98%
“…Ball et al, 1998;Moises et al, 2001); glutamate receptor-modulating synaptic glutamate (GRM3; Egan et al, 2004); serotonin receptor 2A (HTR2A; Moises et al, 2001); serotonin transporter (SLC6A4; Payton et al, 2005) and nicastrin (NCSTN; Deary et al, 2005).…”
Section: Candidate Genesmentioning
confidence: 98%